The relationship between men's peer and social media muscularity ideal discrepancies and body satisfaction. (May 2020) - Flynn, Mark Allen; Cotchett, Emily; Lin, Linda
Previous studies have shown that discrepancy between perceptions of one's actual body type and the ideal bodies of their peers is an important factor for one's body satisfaction. However, there is a lack of research assessing the formation of media-specific discrepancies, the impact of different types of discrepancies together, and discrepancies in adult men. The current study explored the impact of adult men's actual and ideal body perceptions on their body satisfaction. Data were collected on the discrepancies between men's actual muscularity and perceptions of their off-line male and female peers' male ideal, and perceptions of the male ideal from men and women on social networking sites (SNSs). A total of 277 adult men ( M age = 36.55; SD = 11.34) completed a survey online. Actual–ideal discrepancies were present for all four comparison ideals. Overall body satisfaction was significantly linked to the close female friend ideal discrepancy, whereas muscularity satisfaction was connected to all four comparison ideals. Body fat satisfaction was not impacted by any of the discrepancies. The most significant predictor of muscularity satisfaction was the close female friends' ideal discrepancy. Implications suggest the continued use of self-discrepancy theory in new contexts, and continued importance of off-line relationships, despite SNS use.